Average K-, L-, and M-shell fluorescence yields: A new semi-empirical formulae. (January 2023) - Meddouh, K.; Daoudi, S.; Kahoul, A.; Sampaio, J.M.; Marques, J.P.; Parente, F.; Aylikci, N.Kup; Aylikci, V.; Kasri, Y.; Hamidani, A.
Abstract: Theoretical, experimental, and analytical methods for the calculation of K-, L-, and M-shell fluorescence yields ( ω K, ω L, a n d ω M ) of different elements are very important because of the large number of their applications in various areas of physical-chemistry, and medical research. In the present work, all the experimental K-, L-, and M-shell fluorescence yields taken from distinctive sources, for elements with atomic number 4 ≤ Z ≤ 99 for the K shell, 23 ≤ Z ≤ 96 for the L shell, and 40 ≤ Z ≤ 92 for the M shell, are studied. A detailed analysis of these data, and a table with weighted average values ( ω K W, ω L W, a n d ω M W ) of these parameters are presented. New recommended values ω W R are obtained dividing the experimental ratios ( ω EXP ) by the weighted ratios ( ω W ) and removing out-of-range values (less than 0.9 or greater than 1.1). At that point, new values of average fluorescence yields were deduced using an interpolation that involves the well-known analytical function [ ω W R / ( 1 − ω W R ) ] 1 / 4 as function of the atomic number Z, and then semi-empirical data were deduced by fitting the ratio S = ω EXP / ω W R, for the three shells. A comparison was made with other theoretical, experimental, and empirical values reported in the literature. An evident correlation was observed between our result and other works. Highlights: A critical examination of more than 1348 experimental K, L, and M shells fluorescence yields were performed. The collected fluorescence yields cover the period from 1934 to 2021. The recommended weighted average value were used to deduce the semi-empirical fluorescence yields. Reasonable agreement was typically obtained between our result and other works.